1995
DOI: 10.1023/a:1016276613684
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: These results suggest that MCAF may augment the metastastic potential by modulating tumor associated angiogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…For example, CCL2 (MCP-1), which is overexpressed in a wide range of cancers [234], is associated with poor prognosis in breast, colorectal, cervical and thyroid cancers [235][236][237][238][239]. Tumor-derived CCL2 plays a pro-tumor role by recruiting inflammatory monocytes to pulmonary metastases [240] and MDSCs to the tumor microenvironment [241], as well as promoting angiogenesis [242], tumor cell proliferation [243] and migration [244]. On the other hand, CCL2 prevents apoptosis of neutrophils [245] and activates neutrophils in the pre-metastatic lung towards an anti-tumor phenotype where they produce H 2 O 2 to kill disseminated tumor cells [32,66], suggesting a dual role of this chemokine.…”
Section: Neutrophil Activation In Cancermentioning
confidence: 99%
“…For example, CCL2 (MCP-1), which is overexpressed in a wide range of cancers [234], is associated with poor prognosis in breast, colorectal, cervical and thyroid cancers [235][236][237][238][239]. Tumor-derived CCL2 plays a pro-tumor role by recruiting inflammatory monocytes to pulmonary metastases [240] and MDSCs to the tumor microenvironment [241], as well as promoting angiogenesis [242], tumor cell proliferation [243] and migration [244]. On the other hand, CCL2 prevents apoptosis of neutrophils [245] and activates neutrophils in the pre-metastatic lung towards an anti-tumor phenotype where they produce H 2 O 2 to kill disseminated tumor cells [32,66], suggesting a dual role of this chemokine.…”
Section: Neutrophil Activation In Cancermentioning
confidence: 99%
“…Under physiologic conditions, the CCL2/CCR2 chemokine axis plays an important role in the mobilization of inflammatory monocytes from the bone marrow to the blood [36]. Studies had proposed a dual role of CCL2 on tumor growth, and CCL2 can be protective in some tumor models but destructive in others [37, 38]. Overexpression of CCL2 by tumor cells can lead to their destruction by an infiltrate of activated mononuclear cells and may indicate a more favorable prognosis.…”
Section: Recruitment and Characteristics Of Tam In Pancreatic Cancermentioning
confidence: 99%
“…In human breast cancer, it was reported that CCL2 levels in the excised breast cancer tissue were correlated significantly with the level of vascular endothelial growth factor (VEGF), thymidine phosphorylase, TNFa and IL-8, which are potent angiogenic factors (94). Transfection of colon cancer cells with the CCL2 gene induces angiogenesis in a murine model (95). It has been demonstrated that both CCL2 and VEGF expression positively correlates with TAM infiltration and angiogenesis in breast cancer (96).…”
Section: Ccl2 In Prostate Cancermentioning
confidence: 99%